Consumption Effects of Mortgage Payment Holidays : Evidence during the COVID-19 Pandemic - Albuquerque, Bruno (IMF Working Papers; Working Paper, 2022)
We use UK transaction-level data during the Covid-19 pandemic to study whether mortgage payment holidays (PH) can act as a mechanism for smoothing household consumption following negative aggregate shocks. Our results suggest that mortgage PH were accessed by both households with pre-existing financial vulnerabilities and by those with stronger balance sheets, including buy-to-let investors. We also find that the temporary liquidity relief provided by PH allowed liquidity-constrained households to maintain higher annual consumption growth compared to those non-eligible for the policy. Finally, we find that mortgage PH led to higher saving rates for more financially-stable households.